Prognostic of Recurrence of Ankle Sprain Injury in Athletes who Return to Sports Early - Chikih Chikih; Nani Cahyani Sudarsono; Elina Widiastuti; Anggia Prathama Nasution (eJournal Kedokteran Indonesia, 2021)
Ankle sprains can occur in all athletes. The injuries are often considered minor but can occur repeatedly which can cause chronic complications. This evidence-based case report aims to determine the prognosis of recurrent ankle sprains resulting from returning to exercise too early. This report uses two databases for evidence collection, namely PubMed and Cochrane. Of the four articles, it was found that recurrent ankle sprains incidence rate was 33%, and neuromuscular training significantly reduced ankle sprain recurrence rates with relative risk 0.63 (95 % CI: 0.34-0.99) and hazard ratio 0.18 (95 % CI: 0.07-0.43). The healing time to the pre-injury state reached 93.8 ± 1.2 days for conventional therapy and 97.6 ± 1.5 days for a surgical procedure, and the time to return to exercise was 46.6 (95 % CI:15.4-70) days for conventional treatment and 55.2 ± 15.8 (95 % CI: 41.7 ± 9.8) days for surgical procedure. Using an ankle brace can help in healing and preventing recurrent injuries. Future more, proper handling and education about injuries and when is the optimal time to return to exercise can prevent relapse. Keywords: ankle sprain, return to sports, recurrence injury.   Prognosis Kekambuhan Cedera Sprain Pergelangan Kaki Olahragawan Setelah Kembali Berolahraga Lebih Awal Abstrak Cedera sprain pergelangan kaki dapat terjadi pada semua atlet. Cedera tersebut sering dianggap ringan namun jika terjadi berulang dapat menyebabkan komplikasi kronik. Laporan kasus berbasis bukti ini bertujuan untuk mengetahui prognosis kejadian berulang cedera sprain pergelangan kaki akibat kembali berolahraga terlalu awal. Dua basis data digunakan dalam pengumpulan bukti, yakni PubMed dan Cochrane. Dari empat artikel didapati cedera sprain pergelangan kaki dapat terjadi berulang dengan incidence rate 33% dan menyatakan neuromuscular training secara signifikan mengurangi tingkat kekambuhan sprain pergelangan kaki dengan relative risk 0.63 (95% CI: 0.34-0.99) dan hazard ratio 0.18 (95% CI: 0.07-0.43). Waktu penyembuhan ke keadaan sebelum cedera 93.8±1.2 hari untuk terapi konvensional, 97.6±1.5 hari untuk tindakan operatif, waktu kembali berolahraga adalah 46.6 (95% CI:15.4-70) hari untuk tindakan konvensional dan 55.2 ± 15.8 (95 % CI: 41.7 ± 9.8) hari untuk tindakan operasi. Penggunaan penyangga pergelangan kaki dapat membantu proses penyembuhan dan pencegahan cedera berulang. Oleh karena itu penanganan dan edukasi yang tepat mengenai cedera dan menetapkan waktu yang tepat untuk kembali berolahraga dapat mencegah kekambuhan. Kata kunci: cedera pergelangan kaki, kembali berolahraga, cedera berulang.